2020
DOI: 10.18502/ijph.v49i5.3209
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement Effect of Different Doses of Gamma Globulin on the Disease Condition of Infants with Hemolytic Disease of Newborn and Their Effects on Immune Factors in Serum

Abstract: Background: To explore the effect of different doses of Gamma Globulin (GG) on the condition of children with Hemolytic Disease of Newborn (HDN) and the influence of immune factors in serum. Methods: Overall, 180 infants with hemolytic disease of newborn in the People’s Hospital of Zhangqiu Area, Jinan, China from April 2016 to August 2018 were divided into group A (88 cases) and group B (92 cases). Group A was given intravenous low-dose GG on the basis of phototherapy, and group B was given intravenous high-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In addition, this study found that Shenling Chengqi decoction can effectively downregulate serum hs-CRP and TNF in patients with sepsis- α . It can be seen that Shenling Chengqi decoction can enhance the anti-infection effect by improving the immune function, reduce the level of inflammatory factors, reduce the damage of inflammation to tissues and organs, and improve the therapeutic effect [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study found that Shenling Chengqi decoction can effectively downregulate serum hs-CRP and TNF in patients with sepsis- α . It can be seen that Shenling Chengqi decoction can enhance the anti-infection effect by improving the immune function, reduce the level of inflammatory factors, reduce the damage of inflammation to tissues and organs, and improve the therapeutic effect [ 22 ].…”
Section: Discussionmentioning
confidence: 99%